Analisis Status Mutu Air Laut Berdasarkan Metode STORET di Pelabuhan Gilimanuk Bali - Sidauruk, Valenthio; Astawa Karang, I Wayan Gede; Nurweda Putra, I Dewa Nyoman (Journal of Marine Research and Technology; Vol 7 No 1 (2024): FEBRUARI 2024, 2024)
The harbor area has a high risk of pollution. Anthropogenic activities such as ship operations, ship traffic and material used by ships will trigger a decrease in water quality and have a negative impact to the water in harbor area. This study aimed to determined the content of parameters and water quality status at Gilimanuk Harbor, Bali. Samples were taken during the transitional of Summer and Rainy season (September-November 2022) three times with a one-month interval. The parameters used in this study were: temperature, Total Suspenden\d Solid (TSS), pH, salinity, ammonia, lead and coliform. The additional parameters in this study are rainfall, wind and currents to determine the relationship between data. Water quality status in this study was analysed by STORET method, with the water quality standard referenced The Government Regulation Number 22 of 2022 for harbor waters. The parameters that exceeded the water quality standard in this study were Ammonia and the water quality status for the port waters based on the STORET method, specifically at a distance of 50 meters and 500 meters from the shore is class A with (Not Polluted) category while at a distance of 1000 meters from the shore is class B (Lightly Polluted) category. With these results, it can be seen that rainfall, wind and currents have an impact on the distribution of pollutants in the sea water.